GAMBARAN PERILAKU SEKSUAL REMAJA RETARDASI MENTAL DI SEKOLAH LUAR BIASA (SLB) NEGERI SEMARANG - Herini Dwi Widiyanti; Syamsulhuda Syamsulhuda; Anung Sugihantono (Jurnal Kesehatan Masyarakat (Undip), 2016)
Common sexual behavior among teenagers is courting. Adverse effects are courting unwanted pregnancy, sexually transmitted diseases, and so forth. This courtship impact not only in the can on a normal teenager, but teens mild mental retardation as well. With limited intellectual, increase the chances of adolescent mental retardation mild illness, sexual behavior (dating unhealthy). The purpose of this study is to notice the representation of Adolescent’s Sexual Behavior in SLB Negeri Semarang. Research problems in this study is how the sexual behavior of adolescent with mental retardation in the school. This research used the qualitative descriptive method. The subjects of this research were teenagers with mild mental retardation. For the selection of subjects, it used purposive method by 6 people. four men and two women. The data source of this research used primary data and secondary data. Sexual behavior in the courtship of this study. More than half the study subjects knew courtship, but h anya two subjects penelit ian who know healthy dating and only two research subjects said that the impact of courtship is pregnant. SLB Negeri Semarang does not provide the media information that enhances their knowledge related to sexual behavior. There are two research subjects risky sexual behavior accounted for their own sexual behavior to intercourse. This happens because the poor mentoring from teachers and parents. Thus the need for additional knowledge on sexual behavior with appropriate methods and assistance both at school and at home.